Hierarchical and reversible assembly of graphene oxide/polyvinyl alcohol hybrid stabilized Pickering emulsions and their templating for macroporous composite hydrogels. (January 2017) - Chen, Yunhua; Wang, Yilin; Shi, Xuetao; Jin, Min; Cheng, Wenhua; Ren, Li; Wang, Yingjun
Abstract: Control over the reversible assembly of micro- and nano-scopic building blocks is highly important but very challenging in the fabrication of many hierarchical composite materials. Here we report the reversible assembly of emulsion micro-droplets stabilized by graphene oxide/polyvinyl alcohol (GO/PVA) hybrid via simply controlling the hydrogen bonding interaction between GO and PVA. The assembled emulsion droplets at acidic condition can be shaped into different macroscopic objects with a high degree of morphological control through injection molding. Attributed to the reversible hydrogen bonding interactions, the assembled emulsion monoliths/aggregates can be interestingly disassembled back into dispersed droplets when increasing the pH of aqueous phase. Utilizing this GO/PVA hybrid stabilized emulsion as a template, macroporous composite hydrogel was produced via facile polymerization of the aqueous phase, which can be further used for selective payload release, for example, anticancer drug Doxorubicin hydrochloride (DOX). It revealed that DOX release from the composite hydrogels was considerably accelerated when the pH of release medium decreased from 7.4 to 4.0, and the release DOX remained biologically active and had high capability to kill cancer cells, demonstrating the feasibility of using GO/PVA macroporous composite hydrogels as potential drug delivery platforms for cancer treatments.